Laws of Maryland, 1713; Ch. 44, Sect. 32, in The Black Code of the District of Columbia in Force September 1st, 1848, at 11 (1848) - (:unkn) unknown (My University, 1713)
Prohibition on "Negro or other slave" from carrying a gun or offensive weapon off their master's land.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES